2020
DOI: 10.7150/ijbs.44204
|View full text |Cite
|
Sign up to set email alerts
|

ZNF367-induced transcriptional activation of KIF15 accelerates the progression of breast cancer

Abstract: Breast cancer (BC) is one of the most common female cancers, and its incidence has been increasing in recent years. Although treatments are continuously improving, the prognosis of patients in the advanced stage is still unsatisfactory. Thus, an in-depth understanding of its molecular mechanisms is necessary for curing breast cancer. KIF15 is a tetrameric spindle motor which can regulate mitosis in cellular process and exert the crucial functions in several cancers. The purpose of our research was to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…The protein expression of KIF15 in NPC tissues was signi cantly higher than para-carcinoma tissues, which was signi cantly correlated with cancer grades, recurrence and predicted a poor prognosis of patients. Similar results have also been reported in hepatocellular carcinoma [10], lung cancer [12], breast cancer [22] and other tumors [13,23]. All these indicate that the high expression of KIF15 is an unfavorable factor for the prognosis of tumor patients.…”
Section: Discussionsupporting
confidence: 84%
“…The protein expression of KIF15 in NPC tissues was signi cantly higher than para-carcinoma tissues, which was signi cantly correlated with cancer grades, recurrence and predicted a poor prognosis of patients. Similar results have also been reported in hepatocellular carcinoma [10], lung cancer [12], breast cancer [22] and other tumors [13,23]. All these indicate that the high expression of KIF15 is an unfavorable factor for the prognosis of tumor patients.…”
Section: Discussionsupporting
confidence: 84%
“…39 ZNF367 has been reported has a key controller of the neuroblast cell cycle, 40 and it has been reported to accelerate cell cycle progression in breast cancer. 35 Importantly, our rescue experiments confirmed that downregulation of miR-330 in U251 and SHG44 cells restored the levels of PCNA, CDC20, CDC7 and CCNA1, indicating that the GABPB1-AS1/miR-330/ZNF367 axis regulates the cell cycle signaling pathway to govern the malignant behaviors of glioma cells.…”
Section: Discussionsupporting
confidence: 60%
“…Next, ZNF367 was confirmed as a target of miR-330 and was highly expressed in glioma tissues. As a member of the zinc finger transcription factor family, ZNF367 has been reported to accelerate metastasis and progression of breast cancer 34,35 and pancreatic cancer. 36 Here, the subsequent KEGG pathway enrichment analysis suggested that the ZNF367-related genes were enriched on the cell cycle signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The flowchart of literature retrieval process is shown in Supplementary Figure 1. The basic characteristics of all included studies (12,14,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) or datasets are shown in Supplementary Table 2 and Supplementary Table 3.…”
Section: Correlation Analysis Between the Expression Of Kif15 And Pro...mentioning
confidence: 99%